Analisis Pelayanan Publik Di Sentra Pelayanan Kepolisian Terpadu (SPKT) Polres Kota Mojokerto - Rachmad, Imam Zharkasi; Pramono, Sapto (Soetomo Magister Ilmu Administrasi, 2024)
Police agencies are given the responsibility to improve service performance to the community towards striving for excellence (Good Service). In order to improve the performance of the Integrated Police Service Center (SPKT) of the Mojokerto City Police in handling Community Complaints, the ability to manage and administer all work activity processes that are interconnected and interact both internally and externally is required. This research aims to determine public services at the Mojokerto City Police Integrated Police Service Center (SPKT) as well as supporting and inhibiting Faktors for Mojokerto City Police SPKT services. This research uses a qualitative descriptive research method. In collecting data, researchers use interview techniques with informants, after which the results of the interviews will be analyzed. The results of research on public services at the Mojokerto City Police’s Integrated Police Service Center (SPKT) are quite optimal, but there are still several things that need to be improved, such as human resources which are still lacking so services require a little longer time and an internet connection. Supporting Faktors for public services at the Integrated Police Service Center (SPKT) of the Mojokerto City Police are the declaration of an Integrity Zone with the predicate WBK (Corruption Free Area) and WBBM (Clean Bureaucratic Serving Area), friendly and polite service, service in accordance with SOPs, reporting can be done in a timely manner. online via the “My Police” application. The inhibiting Faktors are limited human resources, there are no front office officers, network connections are often disrupted.